Forced Degradation of Flibanserin Bulk Drug: Development and Validation of Stability Indicating RP-HPLC Method - Chew, Yik-Ling; Lee, Hon-Kent; Khor, Mei-Ann; Liew, Kai-Bin; Lokesh, Bontha Venkata Subrahmanya; Akowuah, Gabriel Akyirem (Indian Journal of Pharmaceutical Education and Research, 2022)
Background: Flibanserin had been approved as the first drug by United State Food and Drug Administration (USFDA) for the treatment of female sexual interest/arousal disorder of any severity. However, the stability of this drug has yet to be studied extensively. Objectives: The objectives of this study were to optimize the stability indicating method and evaluate the stability of flibanserin under various forced degradation conditions, determine the order of the degradation kinetics, half-life and shelf life of flibanserin under certain stress conditions. The stability of flibanserin under various stress conditions which would reflect the important aspects of storage condition and excipients which should be avoided in the formulation of this drug substance into final drug products. Methods: Stability indicating method was developed using HPLC. It was validated according to ICH guideline for its linearity, precision, accuracy, robustness, LOD and LOQ. The forced degradation was performed under various stress conditions, namely acidic, alkaline and oxidative conditions (H2O2, AIBN and FeCl3). LC-MS was utilised for identification of the degradation impurities, and the degradation kinetics was evaluated based on the kinetic models. Results: Degradation of flibanserin was noticed under oxidative conditions. Flibanserin was degraded under H2O2 oxidation at room temperature, while AIBN and FeCl3 at elevated temperature. Two N-oxide impurities were identified under H2O2 oxidation. Flibanserin was degraded following the first-order kinetic under H2O2 and AIBN oxidation, while zero-order under FeCl3 oxidation. Half-life and shelf life of flibanserin under respective stress conditions were determined. Conclusion: It is concluded that the RP-HPLC method developed could be used as the stability indicating method in determination of flibanserin stability and its impurities. Flibanserin is sensitive towards oxidative degradation. The impurities and the order of the degradation kinetics were identified.
Keywords: Forced degradation; Flibanserin; Degradation; Active pharmaceutical; ingredients; HPLC; Impurities; oxidation; Degradation kinetics; Stability indicating method